Penggunaan Metode Waterfall pada Website Polytechnic Integrated Online System - W, Wasum; Murtono, Andie; Dharma Arta Kusuma, Dwi; Ilham Ramadhani, Ahmad; Tubagus Tsani Risqi Aji, Ahmad; H. Ndahawali, Daniel (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
In today's digital era, the use of information technology (IT) in public services is a must. One of the implementations is the use of websites in public services. This website is designed to improve information accessibility services to the public (users), making it easier for people to access public services at the Marine and Fisheries Polytechnic of Bitung without having to come to the office. Other benefits that have been felt include more transparent services, the public can see the status of services in real time and help increase campus accountability. In this research, in developing the website, the author used the Waterfall method. The reason for using it is that the stages of work are sequential, interrelated, and easy to develop. After implementing the Waterfall method on the Polytechnic Integrated Online System (PIOnS) website, the results show that it can save time and costs when using public services, accurate, effective, fast, realtime, accountable, and more useful. The next result is that on the PIOnS website there are five types of services, namely Basic Safety Training (BST), Air Blast Freezer (ABF)/Cold Storage, Ship Docking, Ship Machinery Workshop and Training Ship Fleet.